Using synchrotron X‐ray phase‐contrast micro‐computed tomography to study tissue damage by laser irradiation. Issue 9 (23rd August 2016) - Robinson, Alan M.; Stock, Stuart R.; Soriano, Carmen; Xiao, Xianghui; Richter, Claus‐Peter
Abstract : Background and Objective: The aim of this study was to determine if X‐ray micro‐computed tomography could be used to locate and characterize tissue damage caused by laser irradiation and to describe its advantages over classical histology for this application. Study Design/Materials and Methods: A surgical CO2 laser, operated in single pulse mode (100 milliseconds) at different power settings, was used to ablate different types of cadaveric animal tissues. Tissue samples were then harvested and imaged with synchrotron X‐ray phase‐contrast and micro‐computed tomography to generate stacks of virtual sections of the tissues. Subsequently, Fiji (ImageJ) software was used to locate tissue damage, then to quantify volumes of laser ablation cones and thermal coagulation damage from 3D renderings of tissue image stacks. Visual comparisons of tissue structures in X‐ray images with those visible by classic light microscopy histology were made. Results: We demonstrated that micro‐computed tomography could be used to rapidly identify areas of surgical laser ablation, vacuolization, carbonization, and thermally coagulated tissue. Quantification and comparison of the ablation crater, which represents the volume of ablated tissue, and the thermal coagulation zone volumes were performed faster than we could by classical histology. We demonstrated that these procedures can be performed on fresh hydrated and non‐sectioned plastic embedded tissue. Conclusion: We demonstrated that the application of non‐destructive micro‐computed tomography to the visualization and analysis of laser induced tissue damage without tissue sectioning is possible. This will improve evaluation of new surgical lasers and their corresponding effect on tissues. Lasers Surg. Med. 48:866–877, 2016. © 2016 Wiley Periodicals, Inc.